SISTEM PAKAR MENDETEKSI KERUSAKAN SEPEDA MOTOR N-MAX MENGGUNAKAN METODE FORWARD CHAINING BERBASIS ANDROID - Jepon Aprilion Wahyudin Simamora (TeIKa, 2021)
The development of the automatic injection motorcycle industry ini indonesia experienced a very significant development, matic injection motorcycles are more fuel efficient and environmentally friendly, with the high number of automatoc injrction motorcycle user a problem arises that not all injection motorcycle users have the ability to make repairs to thr damage to their motorbikes. With current smartphone technology advancements, bring up an idea or expert system application ideas into smarthphone service quality activities. The system that will be created is “Expert system to detect damage to N-Max motorbikes using Forward chaining method based on Android”. The expert system is to help the user know the damage and make repairs to his motorcycle earlier before there is ongoing damage.